2018
DOI: 10.21037/atm.2018.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Variable selection in Logistic regression model with genetic algorithm

Abstract: Variable or feature selection is one of the most important steps in model specification. Especially in the case of medical-decision making, the direct use of a medical database, without a previous analysis and preprocessing step, is often counterproductive. In this way, the variable selection represents the method of choosing the most relevant attributes from the database in order to build a robust learning models and, thus, to improve the performance of the models used in the decision process. In biomedical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Finally, the combination sets of miRNAs target prediction were solely based on TargetScan database. Thus, the use of efficient genetic algorithms for variable selection in logistic regression model, rather than a linear model, may have advantages to select the clinically optimal markers among all extracted data sets, more accurately 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the combination sets of miRNAs target prediction were solely based on TargetScan database. Thus, the use of efficient genetic algorithms for variable selection in logistic regression model, rather than a linear model, may have advantages to select the clinically optimal markers among all extracted data sets, more accurately 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors used the generation interval, defined as the time needed for an infected person to infect another person and for reproduction rate estimation. The works by Zhang et al ( 35 ) and by Srinivasu et al ( 36 ), Panigrahi et al ( 37 , 38 ), Tamang ( 39 ), Chowdhary et al ( 40 ), and Gaur et al ( 41 ) demonstrated the efficacy of machine learning algorithms in various fields.…”
Section: Related Workmentioning
confidence: 99%
“…Depth from Focus (DFF) [14][15][16] method is an autofocusing method based on focusing search mechanism. DFF method uses a certain definition evaluation function to calculate the definition evaluation function values (evaluation values) of images with different defocusing degrees.…”
Section: Depth From Focusmentioning
confidence: 99%